CARDIOPROTECTIVE EFFECT OF INM 176 ON ISCHEMIA REPERFUSION INJURY USING RAT HEART MODEL - Kumar, Rajan; Khurana, Navneet; Kaur, Barinderjit (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Cardioprotective effect of INM-176 in ischemia reperfusion (I/R) injury in rat heart was evaluated by measuring the extent of release of the enzyme lactate dehydrogenase (LDH) and creatine phosphokinase (CK) and by measuring the myocardial infarction (MI) size. Methods: Five groups of animals were employed. Animals were sacrificed, and heart was mounted over the Langendorff's apparatus. Group I was employed as control group, Group II was the myocardial ischemic (MI) group, and Group III, IV, and V were pre-treated with different doses of INM- 176 (150, 300, and 600 mg/kg). After this, global ischemia accompanied by reperfusion for 30 and 120 minutes was given, respectively. The effluent was collected from coronary vessel before the initiation of ischemia, immediately, after 5 and 30 minutes of reperfusion. The magnitude of myocardial injury was measured by LDH and CK release in coronary effluent. MI size was also evaluated macroscopically using triphenyl tetrazolium chloride staining. Results: In the present study, INM-176 was found to produce a dose-dependent cardioprotective effect against I/R injury, as observed by a decrease in the level of LDH, CK, and infarct size. Pre-treatment with a dose of 600 mg/kg was found to be more effective as compared to 150 and 300 mg/kg dose of INM-176. Conclusion: INM-176 pre-treatment at a dose of 600 mg/kg provides cardioprotection against I/R-induced myocardial injury.